The effects of vocational training and other correctional programmes on the reformation, rehabilitation and reintegration of offenders in Nigerian Correctional Institutions - Mohammed, Hadi (2017)
Reformation, rehabilitation and reintegration programmes are the three main core businesses in the correctional institutions. Both reformation and reintegration programs are housed within the institutions while reintegration is after the offender has been released. Reformation programme includes activities such as moral instruction, counselling, and medical care whereas rehabilitation programme consistsof vocational education and training. Treatment and training are essential to facilitate offenders to reintegrate into society. The purpose of the study is to develop a better understanding of con-ectional programmes on the reformation, rehabilitation and reintegration of offenders in Nigerian correctional institutions. The study used quantitative approach and utilised questionnaire as data collection instruments to gather information on th